2004
DOI: 10.1158/0008-5472.can-03-3492
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in the TGF- β 1 Gene and Breast Cancer Survival

Abstract: The effect of genetic polymorphisms in the TGF-␤1 gene at codon 10 (T؉29C), codon 25 (G؉74C), and the promoter region [C 3 T at ؊509 from the transcription site, (C-509T)] on breast cancer survival was evaluated among a cohort of 1111 patients. The median follow-up time for the cohort was 5.17 years after cancer diagnosis. No DNA sequence variation at codon 25 of the TGF-␤1 gene was found, whereas polymorphisms in C-509T and T؉29C were in strong linkage disequilibrium. Patients who carried the C allele of T؉29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…Age ( Association studies on the polymorphisms of TGFB1 have been conducted previously in breast cancer, 15,[19][20][21][22][23][24][25][26] prostate cancer, 27,28 hepatocellular carcinoma 16,17 and others. [31][32][33][34][35] However, the results from these association studies remain inconsistent rather than conclusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age ( Association studies on the polymorphisms of TGFB1 have been conducted previously in breast cancer, 15,[19][20][21][22][23][24][25][26] prostate cancer, 27,28 hepatocellular carcinoma 16,17 and others. [31][32][33][34][35] However, the results from these association studies remain inconsistent rather than conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 2 common single nucleotide polymorphisms (SNPs) were reported in TGFB1 in an eastern Asian population, [15][16][17] one in the promoter region, C-509T (rs1800469), and the other in the coding region with nonsynonymous amino acid substitution, Leu10Pro (T > C) (rs1982073). Studies have shown that the 2509T allele was significantly associated with higher levels of TGF-b1 than was the 2509C allele.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, homogeneity in terms of ethnic background (98% of study participants were of Han Chinese ethnicity) eliminated race-specific variation in the distribution of genotypes in GSTs. 18 The large sample size and the extended duration of follow-up provided the study with a high level of statistical power. Because the vast majority of study participants (97.8%) underwent mastectomy, potential confounding effects associated with the type of surgical treatment used were not a concern.…”
Section: Discussionmentioning
confidence: 99%
“…18 Almost all patients (n ϭ 1448 [99.2%]) underwent surgery for primary breast carcinoma, and the vast majority of patients completed adjuvant chemotherapy (n ϭ 1369 [93.8%]). In addition, 567 patients (45.0%) received radiotherapy, and 921 patients (77.8%) received tamoxifen treatment, including 906 (76.5%) who received tamoxifen in combination with chemotherapy and/or radiotherapy.…”
Section: Study Populationmentioning
confidence: 99%